Pemanfaatan Instagram Insight dalam Peningkatan Segmentasi Pelanggan pada UMKM Tenun Batik - Efendi Efendi; Abdul Samad Arief; Rizki Dewantara; Pandu Adi Cakranegara; Ade Risna Sari (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2022)
The batik business is engaged by Micro, Small, and Medium Enterprises (MSMEs). In marketing products, there are still MSMEs that use word of mouth (WOMM) in marketing techniques and use WhatsApp communication. Media such as SMEs in the field of batik weaving fashion Muhibbuddiana. This service activity is intended to assist in the use of Instagram in marketing and selling products online, from creating Instagram accounts and product documentation to posting content, as well as analyzing Instagram insights to find out the most popular posts, follower and non-follower interactions, and increase in the number of followers. The activity results show the effect of the ease of using social media on promotion and sales, the impact of using social media to increase sales turnover, and the importance of understanding Instagram insight for customer segmentation.